Hepatic Parenchymal Injury in Crigler-Najjar Type I. Issue 4 (April 2018) - Mitchell, Ellen; Ranganathan, Sarangarajan; McKiernan, Patrick; Squires, Robert H.; Strauss, Kevin; Soltys, Kyle; Mazariegos, George; Squires, James E.
ABSTRACT: Background: Crigler-Najjar syndrome type I (CNI) arises from biallelic variants of UGT1A1 that abrogate uridine diphosphate glucuronosyltransferase (UGT1A1) activity resulting in unconjugated hyperbilirubinemia. Historically, liver parenchyma in CNI was considered structurally and histologically normal. Recent review of CNI liver explants revealed fibrosis. Our aim was to investigate the association between hepatic histology and disease phenotype in CNI. Methods: We extracted data from the medical record at the time of liver transplant from 22 patients with CNI at the Children's Hospital of Pittsburgh, and reviewed explant histology. Continuous data were normally distributed, are presented as mean (±1 SD), and analyzed using two-tailed Student t -test. Categorical data were analyzed using the Chi-square test. Results: Both alanine transaminase (ALT; mean 87.4 IU/L) and aspartate transaminase (AST; mean 54.6 IU/L) were elevated. Nine (41%) of 22 explants had significant fibrosis. Pericentral (n = 5), periportal (n = 2), and mixed (n = 2) patterns of fibrosis occurred. A significant difference in mean age of subjects with fibrotic versus non-fibrotic livers (16.1 years vs 10.5 years; P  = 0.02) was seen. There were no indices of synthetic liver dysfunction or portal hypertension. Neither a history of gallstone disease nor excess weight appeared to contribute to the development of fibrosis. Conclusions: For the first time, we report a 41% prevalence of clinically silent, yet histologically significant fibrosis among subjects with Crigler-Najjar type 1. Risk for fibrosis appears to accrue with time, indicating that earlier intervention may be prudent whenever considering alternative treatments such as hepatocyte transplant, auxiliary liver transplant, or viral gene therapy.